Duplex-imprinted nano well arrays for promising nanoparticle assembly. (19th January 2018) - Li, Xiangping; Manz, Andreas
Abstract: A large area nano-duplex-imprint technique is presented in this contribution using natural cicada wings as stamps. The glassy wings of the cicada, which are abundant in nature, exhibit strikingly interesting nanopillar structures over their membrane. This technique, with excellent performance despite the nonplanar surface of the wings, combines both top-down and bottom-up nanofabrication techniques. It transitions micro-nanofabrication from a cleanroom environment to the bench. Two different materials, dicing tape with an acrylic layer and a UV optical adhesive, are used to make replications at the same time, thus achieving duplex imprinting. The promise of a large volume of commercial manufacturing of these nanostructure elements can be envisaged through this contribution to speeding up the fabrication process and achieving a higher throughput. The contact angle of the replicated nanowell arrays before and after oxygen plasma was measured. Gold nanoparticles (50 nm) were used to test how the nanoparticles behaved on the untreated and plasma-treated replica surface. The experiments show that promising nanoparticle self-assembly can be obtained.